The Essence of Public Relations - Rihma Qoshdatus Salma; Afrida Naila Azmi; Ajeng Sista Kusuma; Raska Pradana; Khusnul Khotimah (Islamic Studies in the World, 2024)
Background. Public relations is the art of creating better public understanding so as to deepen public trust in individuals/organizations. Public relations conveys various important information, both in the context of government, companies and offices. The basic function of public relations is as a transmitter of information and public relations as an information seeker. Purpose. Basically, public relations itself is a modern and structured management tool which is an integral part of an organization or company so that public relations is not a function that is separate from institutional or organizational functions and companies but is attached to company management. Method. This research uses qualitative methods with a focus on natural phenomena without manipulation. Data was collected in depth through library research by reviewing related writings and library sources. Data collection techniques use a literature approach with relevant material. Data sources come from research, writings and published books. Analysis is carried out through reading, investigating and reviewing these sources. Results. Public relations is planned communication between an organization and the public to achieve common goals through understanding and support from the community. Its functions include conveying and searching for information, fostering positive relationships, supporting management, and shaping the organization’s image. Public relations works through two-way communication, both internally and externally, with the aim of creating cooperation and understanding. The role of public relations includes being a liaison, relationship builder, management supporter, and image shaper. Public relations also functions to maintain relationships with internal and external parties of the organization. Conclusion. Public Relations (Public Relations) is planned communication in good faith through the media to gain public recognition, acceptance and support in order to achieve common goals. Its basic functions include conveying and seeking information about organizations and public opinion. The goal of public relations is to create mutual understanding, trust, and cooperation between organizations and the public. His main roles include being a liaison, building positive relationships, supporting management, and shaping the company’s image. Public relations also carries out mutual communication, managing the organization’s internal and external relations as part of its inherent management function.